Bridging Theory To Practice: Applying The Communicative Approach To Improve English Communicative Competence - Ida Bagus Nyoman Mantra; Agne Staupelyte (Laskar Karya, 2024)
This study aims at improving students' communication skills through a communicative approach. The communicative approach makes use of real-life situations that necessitate communication. The teacher sets up a situation that students likely encounter in real life. This study implemented classroom action research. This study found that students' communication skills improved significantly from the first and second cycles. This can be seen from the improvement in the student's achievement of the maximum score in the second cycle. This research implies that it is hoped that the communicative approach can be maximized in English classes so that students can communicate in English meaningfully and effectively.